The loss of government legitimacy - Ali Hamza (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The perversion of administrative deviation and corruption in government and administrative bodies contributes to reducing the legitimacy of the political system in the eyes of the masses. Citizens realize that government officials at various levels are merely elements involved in corruption and are concerned only with the realization of their own interests. As a result, the political system is practically deprived of any Popular support, but show the negative and the reluctance of citizens to cooperate with the existing system and adhere to the system with limited support, for example, from the family or clan to protect him from the pressures of society and the loss of public confidence in public policies and the resulting disruption S serious in the gradual loss of the law of the political system.